A new gm-boosting design technique for wideband inductorless low-noise transconductance amplifiers. (January 2020) - Samavati, Mehdi; Jalali, Mohsen
Abstract: In this paper, a new g m -boosting design technique for wideband inductorless low-noise transconductance amplifiers (LNTA) is presented, resulting in optimal input matching, and noise and linearity performance. The proposed technique in its basic form, relaxes the constraint on transconductance value of conventional g m -boosted common-gate LNTAs so that the overall transconductance can be selected regardless of input matching condition. In addition, the technique can be reconfigured for either optimum noise performance or linearity improvement while imposing negligible power and area overhead. Analytical derivation and practical design procedure for both task is thoroughly discussed. Implemented in a standard 0.18 μm CMOS process, for a reasonable power consumption of 6.7 mW, the proposed LNTA achieves about 24 mS transconductance and a minimum NF of 3.4 dB over a bandwidth of 0.4–2.1 GHz.